77.9k views
1 vote
Solve for y. 2/3+y−1/9=7/9 Enter your answer in the box. y =

User Lonegunman
by
6.0k points

2 Answers

5 votes

Answer:

y = 2/9

Explanation:

Solve for y by simplifying both sides of the equation, then isolating the variable.

User Stephanvs
by
5.9k points
4 votes

Answer:

Value of y in
\bold{(2)/(3)+y-(1)/(9)=(7)/(9)} is
(2)/(9)

Solution:

Given that


(2)/(3)+y-(1)/(9)=(7)/(9)

Now adding
(1)/(9) on both sides,


(2)/(3)+y-(1)/(9)+(1)/(9)=(7)/(9)+(1)/(9)

On simplifying above equation,


(2)/(3)+y=(8)/(9)

On subtracting
(2)/(3) on both sides, we get


(2)/(3)+y-(2)/(3)=(8)/(9)-(2)/(3)

Again simplifying the above equation,


y=(8)/(9)-(2)/(3)

Taking LCM of 3 and 9 and simplify,


y=(8-6)/(9)


y=(2)/(9)

Hence value of y is
\bold{(2)/(9)}

User Jimish Fotariya
by
5.6k points